Patogenesis Diabetes Mellitus Tidak Bergantung Insulin (Non-/fain/in Dependent Diabetes Mellitus) - Ahmad H. Asdie Ahmad H. Asdie (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1989)
The paper described a Short review of mechanism of glucose intolerance in most non-innilin dependent diabetics which is now clear that is not caused by defect in insulin secretion.alone. Genetic predisposition, impaired glucose-mediated insulin secretion, excessive basal hepatiC gluciase production (HGP) and cellular resistance to insulin action have been docuthented in NIDDM:The increase in basal HGP is the primary factor responsible for fasting hyperglycemia, where as both insulin resistance in peripheral tissues and relative defective insulin secretion contribute to the impaired glucose disposal following oral or intravenous glucose administration. Both receptor and post-receptor defects contribute to the insulin resistance observed in non-insulin dependent diabetic patients.The heterogeneity' of NIDDM may present as insulin